In vitro assessment of knee MRI in the presence of metal implants comparing MAVRIC-SL and conventional fast spin echo sequences at 1.5 and 3 T field strength - Liebl, Hans; Heilmeier, Ursula; Lee, Sonia; Nardo, Lorenzo; Patsch, Janina; Schuppert, Christopher; Han, Misung; Rondak, Ina-Christine; Banerjee, Suchandrima; Koch, Kevin; Link, Thomas M.; Krug, Roland (Journal of magnetic resonance imaging, 2015)
To assess lesion detection and artifact size reduction of a multiacquisition variable-resonance image combination, slice encoding for metal artifact correction (MAVRIC-SEMAC) hybrid sequence (MAVRIC-SL) compared to standard sequences at 1.5T and 3T in porcine knee specimens with metal hardware.
First published: 10 June 2014
Gesehen am 23.06.2020